Locked In: Digital Colonialism and the Platformed Prison - Martin, Liam; Mann, Monique (Surveillance & Society)

(untitled) (Surveillance Studies Network, 2025)
This article examines the “prison platform” as a novel technology of digital confinement. The focus is how United States multinational Honeywell established a prison platform in Australia and New Zealand, neighboring settler colonies where the Indigenous peoples never ceded sovereignty, and prison systems continue to be stamped by deeply entrenched patterns of Indigenous hyperincarceration. While studies of digital colonialism have tended to focus on how Global North actors exploit data relations in the Global South, we examine Honeywell building its prison platform across the “North-in-South” divide in Australia and New Zealand, states that are located geographically in the South but have large settler majorities and close ties to the North. We argue that Honeywell exploits the power relations of Indigenous confinement in the settler colony to advance a novel form of tech-facilitated prison privatization. The analysis reveals three key dynamics of prison platforming: the private sector capture of prison infrastructure formally governed by settler state agencies (infrastructural capture), the commercial logic of continual platform expansion through the integration of new data-extracting technologies (extractive integration), and the leveraging of control over infrastructure to entrench power over competitors in commercial markets for prison technology (market gatekeeping). The paper extends research into platform power by shifting focus from online commerce and communications to the built environment of the prison, and spotlights a convergence between cutting-edge digital technology and much older practices of settler colonial social control.